The value of noninvasive scoring systems for the diagnosis of advanced fibrosis in Egyptian patients with nonalcoholic fatty liver disease - Rokaya A Mohamed; Mona I Nabih; Mohamed B ElShobaky; Hany M Khattab (SpringerOpen, 2014)
Background and Objectives Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease that includes a spectrum of liver diseases ranging from simple steatosis to steatohepatitis, fibrosis, and cirrhosis. Liver biopsy is the current gold standard for the assessment of fibrosis in patients with NAFLD. However, it is an invasive procedure and not free from complications. We aimed to analyze the diagnostic performance of simple noninvasive scoring systems for the detection of fibrosis in Egyptian patients with NAFLD. Patients and methods Seventy-six patients with biopsy-proven NAFLD were included in the study. Noninvasive scoring systems included AST/ALT ratio (AAR), APRI score, BARD score, FIB-4 score, and NAFLD fibrosis score (NFS). Patients were classified into two groups according to the grade of fibrosis in liver biopsy. Group 1 included 57 patients with no or mild fibrosis (stage 0-2) and group 2 included 19 patients with advanced fibrosis (stage 3-4). The sensitivity, specificity, positive predictive values, negative predictive values, and diagnostic accuracy for relevant cut-offs and area under receiver operating characteristic curves were determined. Results The area under receiver operating characteristic curves for advanced fibrosis were 0.936 for the FIB-4 score, 0.916 for NFS, 0.907 for the APRI score, 0.840 for AAR, and 0.556 for the BARD score. NFS and the FIB-4 score showed the best diagnostic accuracy (92.6 and 89.7%, respectively), followed by the APRI score (75%), AAR (40.8%), and the BARD score (39.5%). Conclusion FIB-4 and NFS can be used reliably to diagnose or exclude advanced fibrosis in NAFLD and thus reduce the burden of liver biopsies.